A Hybrid Algorithm Based Static Model Updating Method and Its Application to Spacecraft - Jutao Wang; Zhenzhong Liu; Xiaofei Wang (Advances in Materials Science and Engineering)
In some cases, the static model updating requires more precise results to satisfy the requirement of simulating the structural response. The corresponding optimization algorithm not only should have a stronger capability to find the global optimum, but also should achieve an optimal result with high accuracy. The intelligent algorithm and direct searching method have the advantages of global and local optimization, respectively. In the present study, a hybrid strategy based on the intelligent algorithm and direct method are proposed, and a typical test function is initially utilized to test its accuracy. The re-entry module is taken as the case study, whose thermal deformation is used to construct the objective function for optimization, and precise results are achieved. Moreover, the high-accuracy results in different objective functions are obtained. In order to investigate the prediction capability of the proposed method, the displacements in another structural direction are extracted and show high accuracy, which demonstrates the feasibility and efficiency of the proposed approach. The results show that the hybrid algorithm can achieve a better result than the single algorithm in the static model updating.